PERBAIKAN PEMBELAJARAN MENGGUNAKAN STRATEGI PEMBELAJARAN BERBASIS KECERDASAN MAJEMUK TIPE MATEMATIKLOGIS TERHADAP HASIL BELAJAR IPS SISWA TAHUN PELAJARAN 2012/2013 (STUDI SISWA KELAS 3 SDN KOKOP 1 KECAMATAN KOKOP) - Abd Rahman (Widyagogik, 2015)
The success of the learning objectives is determined by many factors including the factor of the teachers in implementing the learning process, because teachers can directly influence, creating and improving intelligence and skills of the students. To overcome the above problems and to achieve the goal of education to the maximum, the teacher's role is very important and teachers are expected to have a method / model of good teaching and learning models are able to choose appropriate and in accordance with the concepts of subjects that will be delivered. The purpose of this action research are: (a) Describe the implementation of improvement of learning Indonesian narrative text reading material with your reading method in class IV SDN Kokop 1 school year 2013-2014. (B) Describe the improvement of learning outcomes Indonesian narrative text reading material in grade IV SDN Lessons Kokop 1 year 2013-2014. This study used action research (action research) as much as two rounds. Each round consists of four phases: design, activities and observation, reflection, and refisi. The targets of this research was grade IV SDN Kokop 1 of the school year 2013-2014. Data obtained in the form of a formative test results, observation sheet teaching and learning activities. From the analyst found that student achievement has increased from cycle I to cycle II. Percentage mastery learning in pre-cycle is 53.3% using conventional teaching methods. After using your reading in the first cycle obtained mastery learning which decreased from pre-cycle is 50% and in the second cycle to be improved from the results of reflection, learning completeness sehinggan increased by 87.5%. so it can be concluded that the learning outcomes of students from the first cycle to the second cycle by using the method of increasing your reading.